An evaluation of the IRI-Plas-TEC for winter anomaly along the mid-latitude sector based on GIM-TEC and foF2 values. Issue 10 (15th November 2019) - Gordiyenko, G.I.; Maltseva, O.A.; Arikan, F.; Yakovets, A.F.
Abstract: Total Electron Content (TEC) has become one of the most widely used observable parameters of the ionosphere. IRI-Plas is an empirical climatic model of the ionosphere and plasmasphere that extends up to GPS orbital height of 20, 000 km. The purpose of the study is to reveal whether the winter anomaly (a phenomenon where the mid-latitude daytime NmF2 (or foF2) is greater in winter than in summer at approximately the same solar activity level) occurs in TEC over the Asian sector and how well it is "captured" by IRI-Plas. The study is based on GPS-TEC data derived from Global Ionospheric Maps (GIM-TEC) for January and July months of high (2000), low (2009) and moderate (2012) levels of solar activity. Ionosonde data recorded at a number of mid-latitude Russian and Kazakhstan ionospheric stations in winter and summer seasons for different levels of solar activity are used along with corresponding IRI-Plas calculations to illustrate some specific features of seasonal variations of the midlatitude ionosphere. A comparative study made between IRI-Plas-foF2 and ionosonde foF2 indicates that the IRI-Plas-foF2 variations are found to be in good agreement with the observations showing similar structures, similar magnitudes reflecting the winter anomaly in the diurnal variations. When the IRI-Plas-TEC values are examined for the difference between winter and summer seasons, it is found that their variations are mainly similar to those of IRI-Plas-foF2. Different from that of IRI-Plas-TEC, the winter anomaly in GIM-TEC is not so strong, appears for both high and moderate levels of solar activity, and it is more pronounced at higher latitudes. In low solar activity, the winter anomaly in GIM-TEC is almost absent at the region considered. Finally, the comparison of the IRI-Plas-TEC and GIM-TEC results for winter conditions show that the IRI-Plas-TEC values are significantly larger than those of daytime GIM-TEC at all locations of Russia and Kazakhstan and for all levels of solar activity that coincides with results of previous studies. However, unlike the previous studies, in summer solstice, IRI-Plas-TEC systematically underestimates the GIM-TEC values during high solar activity year and mostly overestimates them for low solar activity. In moderate solar activity year, IRI-Plas-TEC and GIM-TEC values are practically comparable. Thus, the IRI-Plas-TEC model represents the seasonal anomaly observed in foF2 in mid-latitude region for all levels of solar activity but there is a certain deviation from the behavior of GIM-TEC. One of the main reasons of this discrepancy may be the difference of the model Ne(h)-profile from a realistic profile in the upper ionosphere and plasmasphere, that demands additional updating of models for those upper atmosphere regions.